Pengembangan Inovatif Sistem Pengukuran Kelelahan Berbasis Website untuk Pekerja Industri Konstruksi - Ihsan, Ihsan; Sumardiyono, Sumardiyono; Hastuti, Heni (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Construction workers, who work in physically and mentally demanding environments, experience high levels of fatigue, which is a major cause of accidents and occupational illnesses. Therefore, real-time measurement of fatigue is critical to managing the safety and health of construction workers. This study presents an innovative approach to measuring both subjective and objective fatigue through an integrated web-based system using reaction timer technology as a responsive digital measurement tool. The system has been developed using a flexible open source platform (WordPress) with the integration of specialized plug-ins for the automatic collection and analysis of fatigue data. The research method consists of two stages: (1) the development of an integrated fatigue measurement system for construction workers, and (2) a validation study to assess the feasibility of this method by comparing it with traditional methods such as reaction timers and KAUPK2 questionnaires, together with feedback from construction workers in the field (N=60). Participants were divided into three groups: the website group (N=20), the reaction timer group (N=20), and the questionnaire group (N=20). Results: Based on standardized measurements, participants were classified into three fatigue groups: high (6.67%), moderate (70%) and low (23.33%) across all measurement methods. Quantitative results showed statistically significant differences between the three types of fatigue measurement groups. Conclusions: This study highlights the advantages of the web-based system, which is accessible in real time and facilitates the continuous monitoring of fatigue at work. This innovation has the potential to improve the safety management of construction workers through the collection of relevant data and the integration of digital technology, which can be further developed in future research. Keywords: Fatigue; Construction Industry Workers; Website; Work Fatigue Measurement